The Effect of the (Se) percentage on Compositional, Morphological and structural properties of Bi2(Te1-xSex)3 thin films - Shallal, Ikhlas H.; Al-Attar, Falah I.Mustafa; Hussain, Hadeel F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Alloys of Bi2[Te1-x Sex]3 were prepared by melting technique with different values of  Se percentage (x=0,0.1,0.3,0.5,0.7,0.9  and 1). Thin films of these alloys were prepared by using thermal evaporation technique under vacuum of 10-5 Torr on glass substrates, deposited at room temperature with a deposition rate (12nm/min) and a constant thickness (450Â±30 nm). The concentrations of the initial elements Bi, Te and Se in the Bi2 [Te1-x Sex]3 alloys with different values of Se percentage (x), were determined by XRF,The morphological and structural properties were determined by AFM and XRD techniques.  AFM images of Bi2[Te1-x Sex]3 thin films  show that the average diameter and the average surface roughness increase with the increase of the percentage of Se. The Xâ€“ray diffraction measurements for bulk and thin films of Bi2[Te1-xSex]3 have polycrystalline structure with rohmbohedral structure, with space group R3m, and a strong (015) preferred orientation, the crystallite  increase with the increase of Se percentage .